Meningkatkan kemampuan mengenal angka pada anak usia dini melalui permainan ular tangga di taman kanak-kanak sadar bakti sungai aur pasaman barat - Yuliarti Yuliarti (JRTI (Jurnal Riset Tindakan Indonesia), 2018)
The goal to be achieved from this study is to improve the ability to recognize numbers in children through a snake ladder game in Sadar Bakti Kindergarten, Sungai Aur Pasaman Barat. The type of research is Classroom Action Research conducted by means of cycles, namely two cycles each cycle of three meetings. The results of the study showed that the ability to recognize numbers in children had not yet developed and continued improvement in the first cycle through snake ladder activities using various media. In cycle II achieve optimal results with excellent results. Thus it was concluded that the snake ladder game with various media can improve the ability to recognize numbers in children in the Sadar Bakti Kindergarten, Sungai Aur Pasaman Barat.